(untitled) (Environment & Health, 2021)
Objective: We developed the simplified formulas for the calculation of carcinogenic risk in case of inhalation and cutaneous entry of drinking water chloroform into the human body. Materials and methods: We calculated average daily lifetime doses for the oral, inhalation and cutaneous entry of drinking water chloroform into the human body according to the R.2.1.10.1920-04 and MU 2.2.4-122-2005. The calculation of carcinogenic risks was carried out taking into account the average daily entry of a chemical substance throughout life and the slope factor. Mathematical calculations were performed with the help of the STATISTICA 10 portable software package. Results: In the calculation of the carcinogenic risks, the formulas for the determination of the average daily dose for the inhalation and cutaneous routes of entry of carcinogen into the human body are more complex in comparison with the oral route with additional calculations, reference values, coefficients, etc. Therefore, we have developed a simplified method for its assessment. Linear regression models were chosen to describe the dependence of the carcinogenic risk in the inhalation and cutaneous routes of entry on the concentration of chloroform in water. Evaluation of the results obtained by the values of the correlation coefficients (R, RI), Fisher’s criterion (F, pF), and errors of the coefficients (p) showed that both models were adequate to the initial data with a very high degree of reliability. Conclusions: As a result of the study, the solutions of the problem of the assessment of the carcinogenic health risk from the entry of chloroform with drinking water by inhalation and cutaneous routes were obtained with the help of simplified mathematical formulas of linear dependence. The advantage of the proposed solution method is a speed and ease of getting value of the individual carcinogenic risk for the population of various cities of Ukraine for each route of entry, based on the chloroform content in drinking water. This will make it possible to apply risk assessment for a comparative assessment of the impact of chloroform in drinking water at different territories, in different periods of time before and after preventive measures, to compare the effectiveness of the introduction of new technological processes and equipment, etc.